Retrograde Placement of Ring-Bolster Retained Tubes Facilitates Gastrostomy to Gastrojejunostomy Revision in Children with Esophageal Pathology and Microgastria - Parra, Jorge; Jeyakumar, Arthie; Chick, Jeffrey Forris Beecham; Smith, Caitlin A.; Bertino, Frederic J.; Monroe, Eric J. (Journal of Clinical Interventional Radiology ISVIR, 2021)
Techniques for gastrostomy revision to gastrojejunostomy within the pediatric population, who have failed initial tube placement due to obstructive pathologies, have not been well established. Novel techniques are required to improve outcomes for these patients, and these techniques must be evaluated for both viability and safety. This article describes a technique utilized for gastrostomy to gastrojejunostomy revision and the outcomes for three pediatric patients.
Keywords: dysphagia; nutrition; gastrostomy; gastrojejunostomy; enteric access; esophageal atresia; tracheoesophageal fistula